Estrategias de comunicación digital de Supermercados Tía, en meses de pandemia 2020 - Meneses Preciado, Stefany Mishelle (2020)
In this paper, an investigation is carried out on various points of digital communication, such as the digital communication strategy, which is very important in modern times, especially for companies of all levels, that is, both that are just starting, such as those that have been in the market for years and have already gained prestige, and the way in which the Corporation Tía SA uses communication strategies in times of pandemic will be studied, which provide them with evident success. Its purpose is based on knowing and sharing this information with Babahoyo retail supermarkets, so that they can also implement this type of strategies and methods, which will allow them to improve their current sales and keep their consumers in the long term. In other words, this investigative work aims to serve as an example for small supermarkets, so that they obtain the knowledge they need. This research is non-experimental, since it deals with an analysis and information only work, the results of which were obtained through research, analysis and comparison of various web sources, in addition to conducting a short interview.